2021
DOI: 10.1111/liv.14857
|View full text |Cite
|
Sign up to set email alerts
|

SPARC inhibition accelerates NAFLD‐associated hepatocellular carcinoma development by dysregulating hepatic lipid metabolism

Abstract: Background and aims Non‐alcoholic fatty liver (NAFLD) and its more serious form non‐alcoholic steatohepatitis increase risk of hepatocellular carcinoma (HCC). Lipid metabolic alterations and its role in HCC development remain unclear. SPARC (Secreted Protein, Acidic and Rich in Cysteine) is involved in lipid metabolism, NAFLD and diabetes, but the effects on hepatic lipid metabolism and HCC development is unknown. The aim of this study was to evaluate the role of SPARC in HCC development in the context of NAFL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 58 publications
0
15
0
Order By: Relevance
“…Mazzolini et al [ 93 ] associated low levels of this organokine as a protective factor against NASH and reduced liver damage in morbidly obese patients. In turn, its absence has been related to alterations in the hepatic lipid metabolism and the risk of developing hepatocellular carcinoma, which is closely related to NAFLD [ 94 ].…”
Section: Organokinesmentioning
confidence: 99%
“…Mazzolini et al [ 93 ] associated low levels of this organokine as a protective factor against NASH and reduced liver damage in morbidly obese patients. In turn, its absence has been related to alterations in the hepatic lipid metabolism and the risk of developing hepatocellular carcinoma, which is closely related to NAFLD [ 94 ].…”
Section: Organokinesmentioning
confidence: 99%
“…And moreover, the previous study showed that microRNA-211 could suppress liver cancer cell proliferation and invasion by targeting SPARC, which indicated that SPARC overexpression might drive progression of LIHC ( Deng et al, 2016 ). However, by using a non-alcoholic fatty liver (NAFLD)-related HCC murine model, Onorato et al (2021) found that the absence of SPARC accelerated HCC development, which is associated with an altered hepatic lipid metabolism. And moreover, the study by Atorrasagasti et al also showed that SPARC overexpression in hepatocellular carcinoma cells results in a reduced tumorigenicity partially ( Atorrasagasti et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…The causing factors such as genetic factor (e.g., the genetic variant I148M of rs738409 in patatin-like phospholipase domain containing 3, PNPLA3) and epigenetic factors (e.g., histone deacetylase) for NAFLD and NASH may result in liver fibrosis and cirrhosis, and finally leading to the development of HCC (14)(15)(16)(17). In addition, several other factors including environmental factors have been identified to be associated with NAFLD-related HCC progression (18), such as lipid metabolism (19), and dysregulation of gut microbiota (20). For example, dysregulation of lipid metabolism in NAFLD induced hepatic accumulation of linoleic acid and subsequent loss of CD4 + T cells due to an increase of reactive oxygen species (ROS) (21), resulting in an increased incidence of HCC.…”
Section: Factors Causing Nafld and Nafld-related Hcc Progressionmentioning
confidence: 99%